Perception of nursing profession – focus group interview among applicants to nursing education. - Glerean, Niina; Hupli, Maija; Talman, Kirsi; Haavisto, Elina (Scandinavian Journal of Caring Sciences, 2019)
Aims and objectives: To explore nursing applicants' perceptions of the nursing profession and to identify the factors influencing their perceptions. Background: Perceptions guide the career choice in nursing and the retainment in the profession. Perceptions of nursing profession are said to be outdated and unrealistic among public. Therefore, more information is needed about the perceptions of nursing applicants. Design: Exploratory qualitative design using focus group interviews. Methods: Three focus group interviews (n = 18) were conducted among applicants to undergraduate Bachelor of Science (BSc) nursing programmes. The focus group interviews were recorded transcribed and analysed using qualitative content analysis. In this study, the ethical principles set by Finnish law and the National Advisory Board on Research Ethics were followed. Findings: Applicants perceived nursing through characteristics of a nurse, content of nursing work, nature of nursing work and career possibilities in nursing. According to applicants, nursing requires suitable attitude and character with knowledge, theoretical competence and good general education. Nurses were seen to work in multi‐professional teams and tasks of a nurse were described through caring role of a nurse. The decision‐making in nursing was regarded limited. Nursing was considered as secure job with versatile career options although the career options or the further educational possibilities were not fully recognised among applicants. Personal factors, family and friends, media and career counselling at school influenced applicants' perceptions. Conclusions: Applicants' perceptions of the nursing profession are one‐sided and partly unrealistic. Future research should concentrate on planning interventions aiming to change the public image of the nursing profession.